Analisis Tingkat Kesadaran Masyarakat dalam Membayar Zakat Pertanian di Desa Plakpak Pegantenan Pamekasan - Bariyah, Choiril (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2024)
Plakpak Village, Pegantenan District, Pamekasan Regency, is a village in Pemekasan Regency where the most of the population earns their income from agriculture. Agricultural zakat is one of the obligations that must be fulfilled, but participation in carrying out agricultural zakat is considered to be very lacking in almost all regions. This research purposeful to see how farmers in Plakpak Village understand how to pay agricultural zakat and its relationship with the welfare of farmers in terms of the benefits that agricultural zakat bring to farmers. The procedure used is quantitative descriptive. Farmers in Plakpak Village, Pegantenan District, Pamekasan Regency already have an explanation of agricultural zakat, although they have not yet studied in depth the concept and procedures of agricultural zakat, such as calculations and nisab. Understading of paying agricultural zakat is still low among rice farmers in the area. Of the 5 farmers World Health Organization were informants, only 20% or 1 farmer had paid his agricultural zakat, while 80% or 4 other farmers had not done so.